Intravenous Oxytocin Versus Oxytocin Combined with Misoprostol in the Management of the Third Stage of Labor in Vaginal Delivery - Naheed Fatima, Tehmina Kanwal, Sumbal Andleeb Choudhary, Saadia Zia, Hira Iram, Lubna Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study was aimed to compare the treatment of the third stage of labour in vaginal delivery between intravenous (IV) oxytocin and IV oxytocin + sublingual misoprostol in primigravida with singleton pregnancy. Background: Worldwide, over 290,000 women pass away each year either during pregnancy, labour, or the first six weeks following delivery. The most frequent primary cause of maternal mortality in underdeveloped nations is still postpartum haemorrhage (PPH). To prevent atonic postpartum haemorrhage, uterotonic medications are employed. These medications include misoprostol, oxytocin, carbetocin, and methylergometrine. Numerous studies have shown that oxytocin is the best heat-labile agent for halting blood loss. Study Design: randomized control trial Place and Duration: This study was conducted at Federal Government Polyclinic Hospital PGMI Islamabad from November 2021 to November 2022. Methodology: Participants in the study included 40 cases each group of patients. For the study, we used a single blind randomization to allocate the patients in defined groups. Data were entered into SPSS version 23.0. P-value was calculated using the Chi Square test (for categorical dependent variable) and t-test (for numerical dependent variable). Results: Out of 80 cases in the study, 40 were given oxytocin combined with misoprostol combination and 40 received only oxytocin. Greater than 500 mL blood loss occurred more frequently (27.5% versus 17.5%) in the oxytocin group than in the oxytocin combined with misoprostol combination group. However, the statistical significance of this proportional difference was not established (p-value, 0.08). Out of the 80 total cases, this study indicated that 18 (22.5%) women experienced postpartum hemorrhage. Conclusion: According to the current research, sublingual misoprostol and intravenous oxytocin work better together than they do separately. In comparison to the IV oxytocin alone, the mean blood loss in the combination group was significantly lower. Keywords: Oxytocin, Misoprostol, PPH (Post partum hemorrhage)